PEMBEKALAN PEMBELAJARAN MENDALAM BERBASIS LINGKUNGAN SEKOLAH BAGI MAHASISWA ASISTENSI MENGAJAR PROGRAM STUDI PENDIDIKAN BIOLOGI - I Made Subrata; Yoseph Rano Berto (Program Studi Pendidikan Biologi Universitas PGRI Mahadewa Indonesia, 2026)
Biology is the study of living things, both existing and extinct. Biology learning becomes more contextual when conducted within a school environment. In relation to the immersive learning approach, environment-based learning can increase awareness, meaning, and enjoyment. These three learning principles are implemented through thought, heart, feeling, and exercise. These four efforts are an integral part of education that shapes the whole person (personality or character). The Teaching Assistance Program in the Biology Education study program is crucial for implementing school-based learning within high school (SMA) units. Every essential material in each phase is taught by maximizing the school environment. This article is based on the concept of learning activities carried out for each essential material in phases E and F of high school (SMA) units.